The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ceb.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Motor–cargo adaptors at the organelle–cytoskeleton interface

Abstract: Cytoskeletal motors of the dynein, kinesin and myosin superfamilies maintain and adapt subcellular organelle organization to meet functional demands and support the vesicular transport of material between organelles. These motors require the capacity to specifically recognize the vesicle/organelle to be transported and are capable of selective recognition of multiple cargo. Recent studies have begun to uncover the molecular basis for motor recruitment and have highlighted the role of organelle-associated 'carg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 66 publications
0
76
0
Order By: Relevance
“…We found that transport of both mitochondria and RNA granules in sMNs is perturbed by arginine-rich DPRs. Given the widespread roles of kinesin-1 and dynein in intracellular transport (83,84), as well as our discovery of other classes of microtubule motors in the PR30 interactome from sMNs, it is likely that the trafficking of several cargoes is disrupted by these peptides. Whether altered translocation of a specific cargo type is of particular significance for C9-ALS/FTD remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…We found that transport of both mitochondria and RNA granules in sMNs is perturbed by arginine-rich DPRs. Given the widespread roles of kinesin-1 and dynein in intracellular transport (83,84), as well as our discovery of other classes of microtubule motors in the PR30 interactome from sMNs, it is likely that the trafficking of several cargoes is disrupted by these peptides. Whether altered translocation of a specific cargo type is of particular significance for C9-ALS/FTD remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal circuit connectivity relies on precise spatial and temporal delivery of specific organelles and vesicles to different neuronal subcellular compartments (Tojima et al, 2007, 2011; Akiyama et al, 2016). In this context, different regulatory and adaptor proteins are emerging as critical to assist opposite teams of molecular motors in their fine-tuned delivery of specific cargoes in developing neurons (Akhmanova and Hammer, 2010; Fu and Holzbaur, 2014; Schlager et al, 2014; Cross and Dodding, 2019; Olenick and Holzbaur, 2019). Although in vitro studies have highlighted the importance of the regulation of cargo transport velocity for axon outgrowth (Schlager et al, 2010, 2014), an in vivo role for such mechanisms in axon navigation processes is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesore treatment results in dynamic looping and bundling of microtubules within the cytoplasm and their extrusion from the cell body as membrane-bound projections. This renders microtubules from within the cell accessible for cryo-EM studies (Cross and Dodding, 2019;Randall et al, 2017). Here we describe the discovery of filamentous actin (F-actin) inside the microtubule lumen through in situ cryo-electron tomography (cryo-ET) analysis of these small molecule-induced projections.…”
Section: Introductionmentioning
confidence: 99%